2016
DOI: 10.14260/jemds/2016/346
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Susceptibility Pattern of Klebsiella Pneumoniae Isolated From Cases of Urinary Tract Infection in a Tertiary Care Setup

Abstract: Urinary Tract Infection (UTI) is second on the ranking of most common infection in community practice. It leads to significant morbidity and a high economic burden for treatment. Klebsiella pneumoniae accounts for 2 nd highest organism isolated from urine samples of UTI patients after Escherichia coli. The management of UTI is complicated by the increasing prevalence of antibiotic resistant strains of Klebsiella pneumonia. Therefore, knowledge of the antibiotic resistance patterns of the pathogen is important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
(21 reference statements)
2
4
0
Order By: Relevance
“…Besides chloramphenicol, ceftazidime, and ciprofloxacin, results of the present study indicate that meropenem is one of the most effective antimicrobials against Klebsiella species since the isolates demonstrated susceptibility ranging from 66.7% to 100%. This was in agreement with another study in India where 65.7% of K. pneumoniae were meropenem susceptible [ 36 ]. A 2018 study conducted in Germany also revealed that the carbapenem nonsusceptibility in K. pneumoniae isolates is still low even though it is slowly growing and in the light of the strong increase of K. pneumoniae isolates over the last year; this poses a significant challenge to public health [ 37 ].…”
Section: Discussionsupporting
confidence: 93%
“…Besides chloramphenicol, ceftazidime, and ciprofloxacin, results of the present study indicate that meropenem is one of the most effective antimicrobials against Klebsiella species since the isolates demonstrated susceptibility ranging from 66.7% to 100%. This was in agreement with another study in India where 65.7% of K. pneumoniae were meropenem susceptible [ 36 ]. A 2018 study conducted in Germany also revealed that the carbapenem nonsusceptibility in K. pneumoniae isolates is still low even though it is slowly growing and in the light of the strong increase of K. pneumoniae isolates over the last year; this poses a significant challenge to public health [ 37 ].…”
Section: Discussionsupporting
confidence: 93%
“…The current nding pointed out that meropenem was the most effective antibiotics against ESBLproducing and non ESBL producing Klebsiella species as it showed sensitivity of 80 and 100% in ESBL producers and non ESBL producers Klebsiella isolates respectively. This was in agreement with a study conducted in India, meropenem (65.7%) sensitivity (28).…”
supporting
confidence: 93%
“…After incubating at 37 0 C for 24 hours, a ≥5mm increase in the zone diameter in comparison to ceftazidime were taken as indicative for ESBL positive/producer. Escherichia coli ATCC 25922 was used as an ESBLnegative and Klebsiella pneumoniae 700603 was used as an ESBL-positive reference strain (28).…”
Section: Extended Spectrum β-Lactamase Detectionmentioning
confidence: 99%
“…In the present study only 13.419% positive urine cultures demonstrated growth of klebsiella whereas Savda LA et al demonstrated 60.92% positive for klebsiella growth. 30 32%) was very high but in case of amikacin 67.7% (vs. 59.13%) it was nearly similar 32. Again, Manikandan C. demonstrated high sensitivity to fluoroquinolone group as compared to the present study (ofloxacin 79.2% vs. 30.28%, ciprofloxacin 76.4% vs. 33.65%, norfloxacin 75% vs. 29.32%)29 , but sensitivity of nitrofurantoin is nearly similar (50% vs. 48.07%) 31.…”
mentioning
confidence: 85%